(untitled) (Research, Society and Development, 2023)
Neurilemmoma or Schwannoma is a benign neoplasm of neural origin originating in the Schwann cell, which can be considered relatively uncommon, and which affects soft tissues in the head and neck region, being noted in these regions in 25% to 48% of cases. The diagnosis is made by histopathological examination, and the most indicated treatment is conservative surgical excision, with a favorable prognosis, and the lesion should not recur or present malignant transformations. Thus, the aim of the study is to discuss the main treatments available for Neurilemmoma, through an integrative literature review. This study was carried out from February 2023 to April 2023, through a literature review of scientific articles obtained from the Scielo, PubMed and Google academic databases, in which articles directly related to the theme of the work were included. There are several treatment methods for Neurilemmoma, with surgical excision being the most commonly used method. There are also innovative options, such as the Gamma Knife, and Five-Fraction Stereotactic Radiotherapy with Linear Accelerator, which can be used together to ensure greater treatment efficiency. Surgical excision is still the most used treatment method for Neurilemmomas. However, other methods have been used, with a view to ensuring greater benefit in the treatment.